Encyclopedia of evolution - Pagel, Mark (New York : Oxford University Press, 2002)
"All aspects of evolution, including theories, researchers, history, philosophy, processes, plants, and animals, are covered in this reference work. Other science reference publications include information about evolution, but this source is unique because of its comprehensive and thorough examination of the subject. It includes thought-provoking essays on such topics as culture in chimpanzees, motherhood, and Darwinian medicine, all written by recognized scholars in the fields. Extensive indexing makes any topic easy to locate. This is a crucial research tool for anyone in search of information on any aspect of evolution."--"The Best of the Best Reference Sources," American Libraries, May 2003.
v. 1. Overview essays, ACAN-HYBR , v. 2. IDEA-ZOOT, Index.
Includes bibliographical references and index.
Keywords: Evolution (Biology) -- Encyclopedias